The Relationship Between Family Support And The Quality Of Life Of Tuberculosis Patients In The Kembaran 1 Banyumas Community Health Center Area - Inggrid Fatmah Miharsih; Mariah Ulfah; Madyo Maryoto (CV. AFDIFAL MAJU BERKAH, 2026)
Tuberculosis (TB) is a communicable disease that remains a major public health problem in Indonesia due to its high incidence, long treatment duration, and its impact on patients' physical, psychological, social, and environmental conditions, which can reduce quality of life. Family support is an important factor that plays a role in improving the quality of life of tuberculosis patients. This study aimed to determine the relationship between family support and the quality of life of tuberculosis patients in the working area of ​​Kembaran 1 Public Health Center, Banyumas. This study employed a quantitative analytical method with a cross-sectional design. The sample consisted of 67 tuberculosis patients selected using proportionate stratified random sampling and simple random sampling techniques. The research instruments were the Perceived Social Support from Family (PSS-Fa) questionnaire to measure family support and the WHOQOL-BREF Indonesian version to assess patients' quality of life. Data were analyzed using appropriate statistical tests. The results showed that there was a significant relationship between family support and the quality of life of tuberculosis patients (p < 0.05). Better family support was associated with better quality of life among tuberculosis patients. Family support plays an important role in improving the quality of life of tuberculosis patients.